Fluid intake behavior in athletes during typical training bouts - Buoite Stella, A.; Francescato, M. P.; Sims, S. T.; Morrison, S. A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Hydration habits during training may differ depending on sports mode and individual characteristics. The aim of this study was to assess fluid intake behavior in a wide sample of Italian athletes during their regular training.